SURGICAL TREATMENT OF GASTRIC STUMP CANCER: A COHORT STUDY OF 51 PATIENTS - Eric DRIZLIONOKS; Valdir TERCIOTI JUNIOR; João de Souza COELHO NETO; Nelson Adami ANDREOLLO; Luiz Roberto LOPES (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT BACKGROUND: Gastric stump neoplasia is defined as a neoplasia that arises in the gastric remnant after at least 5 years of interval from the first gastric resection. AIMS: The aim of this study was to analyze 51 patients who underwent total and subtotal gastrectomy and multi-visceral resections in patients with gastric stump cancer. METHODS: The hospital records of 51 patients surgically treated for gastric stump cancer between 1989 and 2019 were reviewed. The following data were analyzed: sex, age group, the interval between the first surgery and the diagnosis of gastric stump cancer, location of the ulcer that motivated the gastrectomy, type of reconstruction, tumor resectability, surgery performed, reconstruction of the digestive tract, associated surgical procedures, postoperative complications using the Clavien-Dindo classification, disease staging, and survival. RESULTS: There were 43 (83.3%) men, with a mean age of 66.9 years. The mean interval between the initial gastrectomy and surgery for the treatment of gastric stump neoplasia was 34.7 years. All had previously undergone Billroth II reconstruction. Most patients underwent total gastrectomy (35 cases – 68.6%), followed by subtotal gastrectomy (6 cases – 11.8%), and the remainder were considered unresectable (10 patients – 19.6%), undergoing jejunostomy for nutritional support. Multi-visceral resections consisted of splenectomies, cholecystectomies, hepatectomies, partial colectomies, pancreatectomies, enterectomies, and nephrectomies. Among the patients who had the lesion resected, the mean follow-up time was 34.2 months (standard deviation: 47.6 months), the overall survival at 3 years was 43.6%, and the survival at 5 years was 29.7%. CONCLUSION: The treatment of gastric stump neoplasia is still challenging and difficult, and personalized follow-up strategies should be focused on high-risk patients, offering opportunities for early intervention, better clinical outcomes, and long-term survival.